Variación en la intensidad de la isla de calor urbana por efecto del cambio climático en ciudades chilenas - Henríquez Ruiz, Cristian; Smith, Pamela; Contreras, Paulina; Qüense, Jorge (Geographicalia, 2021)
Urban Heat Island (UHI) is the main characteristic of the urban climate and is defined as the difference between urban and rural temperature. Its existence is explained by the design and construction materials of the city, impermeable and non-evapo-transpiring surfaces, its effects are of various kinds. The magnitude and intensity of the ICU depends on the size of the city and therefore, the volume of spatially concentrated population. The objective of this research is to propose a methodology that allows estimating the maximum intensity present and future ICU through an approximation of multiple models (climate and land use) and considering the effects of climate change. The results show that the average ICU of the main Chilean cities analyzed is consistent with values from international studies, highlighting the case of Great Santiago, which would have a UCI higher than 10 ºC.
Keywords: Urban heat island, Land use change, Climate change, Oke, ARClim.